Self-perceived licensure examination preparedness of DLSU graduating accountancy students under non-traditional learning: An explanatory sequential design - Alfonso, Erin Angela Pang (Animo Repository, 2023)
The decline in the national passing rate for the Licensure Examination for Certified Public Accountants (LECPA) is a pressing concern as there is an existing shortage of Certified Public Accountants (CPAs) in the Philippines. The COVID-19 pandemic furthered this issue as the abrupt shift to non-traditional learning setup has introduced new challenges in the delivery of quality Accounting education. With limited literature available, this research study employed an Explanatory Sequential Mixed Methods Design to determine the level of self-perceived preparedness among graduating Bachelor of Science in Accountancy (BSA) students in DLSU - Manila under the non-traditional learning setup, and to identify the perceived common factors that affected it. The data collection involved a rigorous process of conducting a survey followed by interviews, which were subsequently analyzed using descriptive statistics and thematic analysis, respectively. Triangulation and complementarity techniques were used to integrate data. Results have shown that graduating BSA students perceived themselves to be moderately prepared for the upcoming LECPA; personal motivation, timing, curriculum design, learning setup, professors, and administrators and course coordinators were identified as perceived common factors that influence it. The findings of the study can serve as a valuable point of reference in enhancing the resilience of the BSA program, enabling it to uphold the delivery of high-quality Accounting education regardless of prevailing circumstances.